ECT 300 Educational Technology: What are some of the limitations of using live radio broadcasts in teaching? - Nasib, Tim (somi, 2017)
CHAPTER 6  EDUCATIONAL BROADCASTING 6a v).Analyze some of the limitations of using live radio broadcasts in teaching. 6.7 Limitations of live radio broadcasts. As mentioned earlier in this unit eve…

Tiyende! Let’s Walk! - Save the Children (2017)
Singilton Phiri Interactive Radio Instruction Specialist Save the Children in Malawi June 16, 2017 Before the introduction of sponsorship in rural Zomba in Malawi, walking...Read the full article...

Interactive Radio Instruction Brings Learning Back to Eastern Democratic Republic of the Congo - War Child Canada (2017)

Exploiter le potentiel des TIC : Programmes efficaces d'alphabétisation et de numératie utilisant la radio, la télévision, la téléphonie mobile, les tablettes et les ordinateurs - UNESCO (UNESCO Institute for Lifelong Learning, 2017)

Philippines: National Demographic and Health Survey - USAID (2017)